MSMEG_6292, a Mycobacterium smegmatis RNA polymerase secondary channel‐binding protein: purification, crystallization and X‐ray diffraction analysis. Issue 9 (10th September 2018) - Joseph, Abyson; Nagaraja, Valakunja; Natesh, Ramanathan
Abstract : The Mycobacterium smegmatis Gre‐factor homologue MSMEG_6292 is an RNA polymerase secondary channel‐binding protein. To understand its structure and function, it was cloned, expressed, purified and crystallized, and crystallographic diffraction data were collected for both the native protein and a platinum derivative. Abstract : The transcriptional activity of RNA polymerase (RNAP) is controlled by a diverse set of regulatory factors. A subset of these regulators modulate the activity of RNAP through its secondary channel. Gre factors reactivate stalled elongation complexes by enhancing the intrinsic cleavage activity of RNAP. In the present study, the protein MSMEG_6292, a Gre‐factor homologue from Mycobacterium smegmatis, was expressed heterologously in Escherichia coli and purified using standard chromatographic techniques. The hanging‐drop vapour‐diffusion crystallization method yielded diffraction‐quality crystals. The crystals belonged to the trigonal space group P 31 21 (or its enantiomorph P 32 21), with unit‐cell parameters a = b = 83.15, c = 107.07 Å, α = β = 90, γ = 120°. The crystals diffracted to better than 3.0 Å resolution. Molecular‐replacement attempts did not yield any phasing models; hence, platinum derivatization was carried out with K2 PtCl4 and derivative data were collected to 3.4 Å resolution.